Sensory Profile of Fruit Wine Made from Local Commodities: A Case Study on Tomato, Amberella, Pomelo, Tamarillo, and Cocoa Wine - Antonia P. Bao; Umbu N. Limbu; Monika M. Meo (Jurnal Biologi Tropis, 2026)
Traditionally, wine is produced using grapes as the raw material because their sugar content and natural acidity are very ideal for yeast growth. However, dependence on grapes limits the utilisation of other horticultural potentials, especially in tropical regions rich in local fruit diversity. Diversification of raw materials through the production of fruit wine becomes a strategic alternative to increase the economic value of local commodities while also reducing post-harvest losses. Ngada Regency has a variety of tropical fruits that can be utilised as a strategic alternative for making fruit wine while also increasing the market value of the fruits. The objective of this research is to evaluate and map the sensory profile, including clarity, colour, aroma, and taste, of fruit wine made from five local commodities (tomato, ambarella, pomelo, tamarillo, and cocoa). The method used is an experiment with a Completely Randomised Design research design consisting of 5 fruit type treatments and 4 replications for each treatment. The stages include the preparation of fruit filtrate, fermentation of fruit wine for 14 days, and sensory profile (organoleptic) testing involving 30 untrained panellists. Data were analysed using the One-Way Anova test. The research results show that out of the five types of fruit wines, tomato wine has a very clear level of clarity, with a golden yellow colour, a characteristic tomato and alcohol aroma, and a taste of alcohol with a slight sweetness. The Anova test indicates a significant difference in the sensory profiles of wines from various local fruits.